Culture (the Right to access to) - Antonino de la Cámara, Mar (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
This voice has been written with a double objective, namely a) to concretize the legal content of the right of access to culture, so we will proceed  b) to analyze some of the most paradigmatic case-law of the European Court of Human Rights in relation to the protection of the culture. Therefore, it is not a theoretical approach to what is culture, but to specify the scope of a right so unstudied within the European geographical framework.
Keywords: Right of Access to Culture; Right to Culture; Right to Freedom of Expression; Right to artistic freedom; European Court of Human Rights; Copyright